3D evaluation of stress concentration factor and stress intensity factor of welded joints - Li, Guiming. (2008)
In this study a coupling scheme of finite elements to boundary elements is implemented for solving any general cracked problems. For the structural analysis of any tubular welded joints with an initial crack, it is well-known that it is time consuming to use finite element method to prepare the mesh of these complex structures since very fine mesh is need. The boundary element method is suitable to analyse any fracture problem, but it is not a wise idea to use boundary element method alone for the full structure of any tubular welded joints with an initial crack. The system matrix of BEM is not symmetric, this will need large amount of CPU time. The combination of finite elements to boundary elements renders an efficient technique for this kind of engineering application. The relationship between nodal displacements and tractions on the interface from finite element equations can be introduced into boundary integral equation as a natural boundary condition. The efficiency of the method is demonstrated by modelling and analysing cracked T-tubular welded joints with an initial semi-elliptical surface crack at the saddle point. The boundary elements are used for stress intensity factors computations in the domain with crack and high stress gradients, and finite elements are used in other parts of the structure with low stress gradients. Numerical results are given to compare the accuracy and efficiency of the method.